Increased Requirement of Replacement Doses of Levothyroxine Caused by Liver Cirrhosis - Benvenga, Salvatore; Capodicasa, Giovanni; Perelli, Sarah; Ferrari, Silvia Martina; Fallahi, Poupak; Antonelli, Alessandro (Frontiers in Endocrinology, 2018)
Background Since hypothyroidism is a fairly common dysfunction, levothyroxine (L-T4) is one of the most prescribed medications. Approximately 70% of the administered L-T4 dose is absorbed. The absorption process takes place in the small intestine. Some disorders of the digestive system and some medicines, supplements, and drinks cause L-T4 malabsorption, resulting in failure of serum TSH to be normal. Only rarely liver cirrhosis is mentioned as causing L-T4 malabsorption. Case report In this study, we report increased requirement of daily doses of l-thyroxine in two patients with the atrophic variant of Hashimoto’s thyroiditis and liver cirrhosis. In one patient, this increased requirement could have been contributed by the increased serum levels of the estrogen-dependent thyroxine-binding globulin (TBG), which is the major plasma carrier of thyroid hormones. In the other patient, we switched from tablet L-T4 to liquid L-T4 at the same daily dose. Normalization of TSH levels was achieved, but TSH increased again when she returned to tablet L-T4. Conclusion Liver cirrhosis can cause increased L-T4 requirements. In addition to impaired bile secretion, the mechanism could be increased serum TBG. A similar increased requirement of L-T4 is observed in other situations characterized by elevation of serum TBG. Because of better intestinal absorption, L-T4 oral liquid formulation is able to circumvent the increased need of L-T4 in these patients.